Transformations of Millennialism in African American Discourse (KULT_online, 2009)
In his dissertation on apocalyptic motifs in American hip hop, Florian Werner examines millennialistic themes in African American discourse from primarily spoken genres of orature. Werner traces the aesthetic roots of contemporary rap, beginning with the earliest documented slave spirituals and continuing on to popular songs from African colonialisation, works of blues, and the "chanted sermons" of African American preachers. Over the course of 255 pages Werner elucidates how popular references to the end of days have changed during each respective historical period.